Perencanaan Instalasi Pengolahan Air Minum di Kecamatan Segedong, Kalimantan Barat dalam Rangka Pemenuhan Target SDGs - Astisza Syahla Ludmilla Parabi; Kiki Prio Utomo; Laili Fitria (Fakultas Teknik, 2022)
Drinking water is an aspect of Sustainable Development Goals/SDGs 2030 with the aim of ensuring the availability and management of clean water and sustainable sanitation. Many efforts to fulfill drinking water have been carried out by the Government of Indonesia, including in Segedong District as evidenced by the existence of a Drinking Water Treatment Plant. However, with the increase in population, the water produced by the WTP cannot sufficient of drinking water needs, so it is necessary to increase the amount of drinking water by planning a Water Treatment Plant for Segedong District for 15 years (2021-2035). The method used is primary data collection (climatological data) and secondary data (population and public facilities) which will then be processed to obtain the amount of drinking water needed and the required WTP capacity. The results obtained that the raw water source comes from the Peniti River, where the Peniti River has parameters that exceed the quality standard, namely color, pH, turbidity, organic matter, manganese, iron, and total coliform. Parameters will be processed with coagulation, flocculation, sedimentation, filtration, disinfection, neutralization. The calculation results show the amount of drinking water needed is 85.56 l/sec. Planning is carried out in 3 stages every 5 years, so that the planning to be carried out is phase I planning for drinking water needs in 2026 with a capacity of 75 l/s. Phase I planning requires an area of 293.97 m2.